An Argument for the Improvisational Design of Customer Service Behaviours - Gaskill, Eddy (Curtin University, 2019)
The thesis examines the role of improvisation in the theory and practice of design for service and management-oriented design thinking. This examination reveals several features that design thinking and improvisation share, which has significance for service innovation - as it suggests that these features might be incorporated into ‘real-time’ service encounters to make service workers’ improvised behaviours more designerly. Manzini’s ‘action platform’ concept is explored, and used to illustrate how design and improvisation might be combined.